Design Of Safety Hoist Lifting System On Electric Container Crane Based Programmable Logic Controller Omron Type CP1E-E20DR-A And Microsoft Visual Basic - Eddo Mahardika; Feri Firmanto; Dwi Songgo Panggayudi (Jurnal Teknik Elektro dan Komputer TRIAC, 2019)
Electric  container  cranes  that  exist  today  still  have  shortcomings  in  the safety hoist lifting system. Safety is less reliable resulting in the accident when the lifting hoist process runs, the case that often happens is the fall of containers during the appointment process. The other problem, safety hoist lifting system can not be monitored by computer in the spreader system. This  study  improves  the  existing  safety hoist  lifting  system deficiencies by designing  and  constructing  the  electric  container  crane  model  which  safe  and efficient using the Programmable Logic Controller Omron CP1E-E20DR-A    as a safety system  and  Visual  Basic as  Human Machine  Interface  (HMI).  PLC  was chosen in  this  study  because it  is  flexible  in  programming.  HMI  program  using Visual Basic and Arduino Uno R3 was chosen because it is cheaper.The use of PLC  in  safety hoist  lifting  system  is very  effective because  the reversible counter and timer programs can replace the functions of cam switches and overspeed switches that are less effective. The addition of HMI proved to be easier in the monitoring system. Safety hoist lifting system in electric container crane safe and efficient can be  built with PLC  and Visual Basic with a  lower  cost  has  been  able  to  provide convenience in the monitoring system.Keywords: container crane, safety, hoist lifting, interlock